Graph-based normalization and whitening for non-linear data analysis - Aaron, Catherine (Neural networks, 2006)
In this paper we construct a graph-based normalization algorithm for non-linear data analysis. The principle of this algorithm is to get a spherical average neighborhood with unit radius. First we present a class of global dispersion measures used for “global normalization”; we then adapt these measures using a weighted graph to build a local normalization called “graph-based” normalization. Then we give details of the graph-based normalization algorithm and illustrate some results. In the second part we present a graph-based whitening algorithm built by analogy between the “global” and the “local” problem.